2023
DOI: 10.3389/fpsyt.2023.1132169
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric properties of the Korean version of questionnaires on adherence to physical distancing and health beliefs about COVID-19 in the general population

Abstract: IntroductionWe aimed to examine the psychometric properties of the Korean version of the questionnaires on adherence to physical distancing and health beliefs about COVID-19 in the general population in South Korea. In addition, we investigated how the various sections interacted with each other and with viral anxiety and depression, and ultimately affected adherence to physical distancing.MethodsAn anonymous online survey was conducted among members of the general population in South Korea between 10 and 18 J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Questionnaires on adherence to physical distancing were already validated in Korea among the general population 34 and healthcare workers. 35 This study showed a good fit for a two-factor model among patients with cancer.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Questionnaires on adherence to physical distancing were already validated in Korea among the general population 34 and healthcare workers. 35 This study showed a good fit for a two-factor model among patients with cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Previous study showed a good fit for a two-factor model for questionnaire on adherence to physical distancing. 34 Factor I focuses on individual’s daily routines and maintaining physical distancing at home, while factor II emphasized the use of masks and protective measures in public spaces.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation